THE ENHANCEMENT OF INFERRING AND COMMUNICATING SKILL THROUGH PROBLEM SOLVING LEARNING MODEL IN COLLOID MATERIAL - Della Amelia; Ratu Betta Rudibyani; Noor Fadiawati (Universitas Lampung, 2012)
The aim of this research is to know effectiveness of problem solving learning model in enhancing inferring and communicating skill in colloid material. Populations were all 227 students of Grade XI science in YP Unila Senior High School in Bandar Lampung. The samples were 36 students in classroom XI science one and 39 students in classroom XI science two that have equal academic abilities. This was a quasi experiment research using non equivalent control group design. Effectiveness of learning with problem solving model was measured based on significant gain enhancement. The result showed that average values of N-gain of inferring skill in experiment and control classrooms were 0.59 and 0.47 respectively; and average values of N-gain for communicating skill in experiment and control classrooms were 0.56 and 0.47 respectively. The hypothesis result test showed that classroom that used problem solving learning model had higher skill in inferring and communicating than classroom with conventional learning model. This indicated that problem solvinglearning model was effective to enhance student’s inferring and communicating skill in colloid material.Keywords: Problem Solving, inferring and communicating skill